Change in Tree Spatial Pattern After Severe Wind Disturbance in Four North American Northern Hardwood and Sub-Boreal Forests - Peterson, Chris J. (Frontiers in Forests and Global Change, 2020)
Growing appreciation for the importance of forest structural features to forest functioning has led to increased focus on tree spatial patterns. While the influence of disturbances on composition and diversity has been well-studied, understanding of how disturbances influence spatial pattern is still far from complete. In particular, very few studies have examined the change in spatial pattern as a result of wind disturbance. Here results are presented for change in spatial pattern after severe wind disturbance in four eastern North American forests. It is hypothesized that, as in other types of disturbances, severe wind will cause an increase in aggregation among survivors, and aggregated distribution of mortality. These trends were indeed observed; at very small distances (e.g. 5-10 m), all four sites showed significantly greater aggregation after wind disturbance. Mortality was also significantly aggregated at three of the four sites, but at different distances. Unexpectedly, at slightly larger distances (e.g. 30-50m), all four sites showed significant decreases in aggregation; it is suggested that this second trend may generalize across disturbance types. A hypothesis proposed by Davis et al. (2005) is that intermediate disturbance severity produces the greatest aggregation; this hypothesis is tested in the four sites reported here, and the hypothesis is rejected. Two refinements to this hypothesis are proposed for further testing in future research.